Corrigendum: Extreme Drought in the Brazilian Pantanal in 2019–2020: Characterization, Causes, and Impacts(Front. Water, (2021), 3, (639204) , 10.3389/frwa.2021.639204) - Marengo, Jose A. [UNESP]; Cunha, Ana P. [UNESP]; Cuartas, Luz Adriana [UNESP]; Leal, Karinne R. Deusdará; Broedel, Elisangela; Seluchi, Marcelo E.; Michelin, Camila Miranda [UNESP]; Baião, Cheila Flávia de Praga [UNESP]; Angulo, Eleazar Chuchón [UNESP]; Almeida, Elton K. [UNESP]; Kazmierczak, Marcos L. [UNESP]; Mateus, Nelson Pedro António [UNESP]; et al. (Frontiers, 2022)
In the original article, there was an error. An author name was incorrectly spelled as Eleazar Chuchón Ângulo. The correct spelling is Eleazar Chuchón Angulo.A correction has been made to the author list, citation, and copyright section.The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
Keywords: biodiversity; drought; fires; Pantanal; river levels